Safety and Efficacy of Polymethylmethacrylate-Collagen Gel Filler for Correction of the Pre-jowl Sulcus: A 24-month Prospective Study - Oscar Hevia (Aesthetic Surgery Journal Open Forum, 2022)
Abstract BackgroundPolymethylmethacrylate (PMMA)-collagen gel is approved for the correction of nasolabial folds and severe atrophic, distensible facial acne scars on the cheek. However, fillers are often used off-label in clinical practice, necessitating additional study of safety and efficacy. ObjectivesTo determine the safety and efficacy of PMMA-collagen gel for the correction of lower face aging, specifically the pre-jowl sulcus. MethodsIn this prospective, single-center, 1-year study (N = 20) and additional 1-year extension (N = 10), 20 patients with a pretreatment score of 2, 3, or 4 on the 5-point Merz Aesthetic Scale for jawline at rest were eligible for treatment with PMMA-collagen gel. Efficacy was measured by blinded review using the jawline scale, Subject and Physician Global Aesthetic Improvement Scale (GAIS) and Subject Satisfaction scores, collected at weeks 4, 12, 26, 52, and 104. ResultsImprovement in jawline score was significant at all posttreatment time points up to 104 weeks (P ConclusionsPMMA-collagen gel is well tolerated and effective for durable correction of the pre-jowl sulcus and jawline. Level of Evidence: 4